# 3(w-3)-3=-4(-6w+2)-72

## Simple and best practice solution for 3(w-3)-3=-4(-6w+2)-72 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 3(w-3)-3=-4(-6w+2)-72 equation:

3(w-3)-3=-4(-6w+2)-72
We move all terms to the left:
3(w-3)-3-(-4(-6w+2)-72)=0
We multiply parentheses
3w-(-4(-6w+2)-72)-9-3=0

We calculate terms in parentheses: -(-4(-6w+2)-72), so:
-4(-6w+2)-72
We multiply parentheses
24w-8-72
We add all the numbers together, and all the variables
24w-80
Back to the equation:
-(24w-80)

We add all the numbers together, and all the variables
3w-(24w-80)-12=0
We get rid of parentheses
3w-24w+80-12=0
We add all the numbers together, and all the variables
-21w+68=0
We move all terms containing w to the left, all other terms to the right
-21w=-68
w=-68/-21
w=3+5/21

`